Francisella noatunensis orientalis EM TILÁPIAS DO NILO CULTIVADAS EM TANQUES-REDE NA BACIA DO RIO ARAGUARI, MG - Carreon, Mariela Moura (2018)
Francisella noatunensis is a pathogen of importance, mainly as it is the cause of Franciselose, which is responsible for high death rates in Nile tilapia. This bacteria is characterized through the presence of granulomas in organs, mainly the spleen. The objective behind this study was to identify and describe anatomopathological and histopathological alterations in Nile tilapia, which have been naturally infected by Francisella noatunensis subps. orientalis (Fno), in the region of the Bacia do Rio Araguari, Minas Gerais, Brazil. The tilapias were collected from four commercial fish breeding nets, with reports of 40 to 60% mortality rates in July, 2017, a month that has a drop in the environmental temperature of the water. The tilapia that presented nonspecific clinical signs were collected, stored in plastic bags with water from their environment and sent in ice for anatomopathological and histopathological evaluations in the laboratory. In the necropsy, there was presence of white nodules, with a granulomatous appearance, in the spleen 59/64 (92.2%), kidney 24/64 (37.5%) and liver 09/64 (14.1%). Lesions were not found in the kidney and/or liver without there being white nodules on the spleen. In the histopathological exam, the spleen was the organ most damaged by lesions 59/64 (92.2%) with severe granulomatous splenitis 27/59 (45.8%) being the most frequent; in the kidney, granulomatous nephritis 52/64 (81.3%) and in the liver, the organ that showed least tissue lesions, with steatosis 35/64 (54.7%), followed by congestion 26/64 (40.6%) and granulomatous hepatitis 23/64 (36.0%). Posteriorly, fragments from the spleen of 50 from among the 64 collected tilapia were sent for molecular identification, in which Fno was detected in 98% (49/50) of the samples, by PCR. Only in the spleen of one of the tilapias there was no Fno detected, however, it is worth noting that this tilapia presented skin lesions and the presence of white nodules were noted during the necropsy. Noteworthy when there were granulomatous simultaneous lesions in the spleen and kidney, there were also observed ulcers on the skin of that animal specimen. This differed significantly, suggesting that the skin lesion is related to the presence of Fno in tilapias, serving as an aid for the producer to suspect the presence of the disease and perform a rapid diagnosis, in order to avoid greater losses. From the aforementioned, one can conclude that the high rate of Fno found in this study characterizes outbreaks in the region, which serves as a warning to the Brazilian fish farming industry and principally those fish producers from the region. Highlighted here is that there are zoonotic species that belong to the group of Francisella spp., for which their potential Fno is still not known, principally in terms of the consumption of tilapia meat.